Prevalence and Correlates of Vitamin D Deficiency in a Sample of 290 Inpatients With Mental Illness - Cuomo, Alessandro; Maina, Giuseppe; Bolognesi, Simone; Rosso, Gianluca; Beccarini Crescenzi, Bruno; Zanobini, Francesco; Goracci, Arianna; Facchi, Edvige; Favaretto, Ettore; Baldini, Irene; Santucci, Aurora; Fagiolini, Andrea (Frontiers in Psychiatry, 2019)
Introduction Vitamin D inadequacy or deficiency (VDID) has been reported in a high percentage of otherwise healthy individuals. Factors that may contribute to the high prevalence of VDID in people with mental disorders include diet low in vitamin D, poor sunlight exposure, decrease in cutaneous vitamin D synthesis, intake of certain medications, poor mobility, excessive alcohol intake and tobacco smoking. VDID has been correlated to a host of adverse conditions, including rickets, osteoporosis, osteomalacia, muscle diseases, depression, cognitive dysfunction, and even certain cancers. Objectives The purpose of this study was to report the prevalence and correlates of vitamin D inadequacy in a sample of 290 psychiatric patients admitted to inpatient or day hospital treatment at the University of Siena Medical Center. Methods We retrospectively evaluated the prevalence of VDID in 290 psychiatric inpatients’ medical records during the year 2017 and evaluated the correlates of VDID in patients with mental illness Results 272 out of 290 patients (94%) showed VDID. Physical activity and regular diet were positively correlated with vitamin D levels whereas age, tobacco smoking, PTH, alkaline phosphatase levels were negatively correlated. Statistically significant differences were found among smokers and non-smokers in all study groups. Conclusions VDID was highly prevalent in our sample. In addition to vitamin D supplementation, psychosocial intervention able to promote and help sustain physical activity, appropriate diet, quitting smoking and sensible sun exposure to prevent and treat VDID in patients with mental health should be implemented, tested and introduced in our clinical practice.